The Supervisory Role of Labor Inspection in the Control of Labor Violations - Alotaibi, Mead Mohammed (Journal of Economic, Administrative and Legal Sciences, 2023)
In light of the recent regulatory developments that the Kingdom of Saudi Arabia witnesses, following the Saudi Vision 2030, the scope of application of labor inspection has expanded. From this point of view, our study came to clarify the oversight role played by the labor inspection in controlling labor violations, and to identify the position of the regulator regarding granting the labor inspector the power of judicial seizure, and to clarify the regular measures to control the labor violation, in addition to stating the position of the regulator in granting the labor inspector the power to choose the most appropriate measure to control labor violations. Moreover, the study aims to examine the extent to which labor violations seized by the inspectors could be objected, and the authorities concerned to consider these objections. The current study used the analytical method to reach its results, as the first part deals with labor inspector’s control of labor violations, and the second part deals with the objection to labor violations. Finally, the study reached significant results, from which, the regulator did not explicitly grant the labor inspector the power of judicial seizure, in addition to the fact that the decision to inflict a labor violation against the facility is not considered a final decision. Based on the results, we have recommended that the regulator should explicitly grant the labor inspector the power of judicial seizure. In addition, the regulator should deal with the conflict of statutory texts with regard to granting the labor inspector the power to choose the most appropriate measure to control the labor violation, and to leave that to the discretion of the labor inspector.